Experimental and theoretical study of absolute intensities of ozone spectral lines in the range 1850–2300 cm-1; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 52, № 3-4 - Barbe A.; Plateaux J. J.; Bouazza S.; Sulakshina O.; Mikhailenko S. N. Semen Nikolaevich; Tyuterev V.; Tashkun S. (1994, 1994)
Title screen